A Framework of Risks in the Context of Industry 4.0, Related to Sustainability. Issue 3 (3rd April 2023) - Szlávik, János; Szép, Tekla
Abstract: We stand on the brink of the Fourth Industrial Revolution, that will fundamentally change our world. Not only the main characteristics of the Industry 4.0 are presented, but the intended and unintended consequences of the digital revolution are also listed. This study examines some of the strongest sustainability indicators of the Fourth Industrial Revolution, applying a sustainability assessment model. Then employing the methodology provided by the Technology Foresight Programme (TFP), a comparison matrix is drawn with respect to values and processes. Results indicate that a comprehensive preliminary sustainability analysis is essential to minimize the negative impacts of Industry 4.0.